Impact of Hormonal Therapy Regimens and Adverse Drug Reactions on Quality of Life in Breast Cancer Patients at Dr. Moewardi Regional General Hospital, Surakarta - Luthfiyanti, Niken; Ichsan, Burhannudin (Sciences of Pharmacy, 2026)
Breast cancer remains the most common malignancy among women worldwide, and hormonal therapy is a cornerstone in the management of hormone receptor-positive cases, although its impact on adverse drug reactions (ADRs) and quality of life (QoL) remains a concern. This study aimed to evaluate the association between hormonal therapy patterns, ADRs, and QoL in breast cancer patients. An observational analytic study with a crosssectional design was conducted at Dr. Moewardi Regional General Hospital, Surakarta, from January to June 2025, involving 64 patients selected through consecutive sampling. Data were collected from medical records and structured interviews. QoL was assessed using the EORTC QLQ-C30 questionnaire, and ADRs were evaluated using the FACT-ES instrument. Bivariate and multivariate logistic regression analyses were performed. Most patients were aged <50 years (60.9%) and diagnosed at an advanced stage (57.8%). No significant associations were found between sociodemographic or clinical characteristics and type of therapy, survival duration, or ADR severity (all p>0.05). The most common ADRs were fatigue (51.6%) and hot flushes (50%). QoL assessment showed good functional status (mean = 79.65) and low symptom burden (mean = 25.06), but poor global health status (mean = 26.30). Cancer stage (p = 0.010) and type of therapy (p = 0.027) were significantly associated with QoL. Multivariate analysis confirmed that advanced-stage cancer (OR = 0.31; 95% CI: 0.14-0.68; p = 0.004) and combination therapy (OR = 0.44; 95% CI: 0.21-0.92; p = 0.024) were independent predictors of poorer QoL. These findings highlight the importance of individualized treatment strategies to optimize patient quality of life.